Explorative study on the application of learning model in virtual classroom during Covid-19 pandemic at the school of Yogyakarta Province - Dewi Nilam; Winda Purnama Sari; Marlinda Mulu (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Since Covid-19 was established as a global pandemic and by National DisasterManagement Authority established the status of a national emergency, the government enact work from home since last March. This makes the learning process changed from classical learning to be non-classical or distance learning. This could be said to be minimal preparation because distance learning decisions are taken suddenly as non-classical learning solutions following work from home and study from home decisions. This study aimed to determine the implementation of online learning activities during the Covid-19 pandemic in Yogyakarta. The technique samples were taken randomly covering 4 districts and 1 municipality in Yogyakarta. These conditions force all parties to try to maximize the learning process with due regard to all aspects of support. The results showed that sequentially the most widely used applications to assist in distance learning were Google Classroom, What‘s Application, and Zoom Clouds Meeting. The majority of teachers still apply learning model in virtual learning. The 3 popular learning models to be applied are Cooperative, PBL and PjBL. The teacher states that the learning model applied is very helpful for their work to realize a virtual classroom, helping students to better understand the material delivered, because it follows the systematic syntax on the learning model used. The application of learning models in each meeting in virtual classrooms was arranged varied to optimize learning and maximize the saturation experienced by students. In addition, various learning methods are applied to support predetermined learning models.